2005
DOI: 10.4049/jimmunol.174.9.5341
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Stimulation of CD8+ T Cells during Infection with Intracellular Bacteria Promotes Differentiation Primarily into a Central (CD62LhighCD44high) Subset

Abstract: During infection with lymphocytic choriomeningitis virus, CD8+ T cells differentiate rapidly into effectors (CD62LlowCD44high) that differentiate further into the central memory phenotype (CD62LhighCD44high) gradually. To evaluate whether this CD8+ T cell differentiation program operates in all infection models, we evaluated CD8+ T cell differentiation during infection of mice with recombinant intracellular bacteria, Listeria monocytogenes (LM) and Mycobacterium bovis (BCG), expressing OVA. We report that CD8+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
102
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 56 publications
4
102
1
2
Order By: Relevance
“…Similar suppressive effects have been reported in ST infection models (42). Our previous observations indicate that BCG is neither a suppressive nor potent inducer of CD8 ϩ T cell responses (24,43). Evaluation of immune responses in vivo vs in vitro can give contrasting results depending on the assays used and relying solely on in vitro results can be misleading (44).…”
Section: Discussionmentioning
confidence: 69%
“…Similar suppressive effects have been reported in ST infection models (42). Our previous observations indicate that BCG is neither a suppressive nor potent inducer of CD8 ϩ T cell responses (24,43). Evaluation of immune responses in vivo vs in vitro can give contrasting results depending on the assays used and relying solely on in vitro results can be misleading (44).…”
Section: Discussionmentioning
confidence: 69%
“…These CD8 ϩ T cells differentiate into a stable population with a CD44 high CD62L high phenotype and the capacity to produce IFN-␥ and IL-2 after stimulation in vitro. Although these T cells have many of the features of typical memory CD8 ϩ T cells, they respond slowly following a secondary challenge with BCG-OVA (41). This may be explained by the slow replication of BCG and/or the low level of OVA produced because challenge of the same memory-immune mice with rOVA-expressing Listeria monocytogenes results in a greater expansion of OVA-specific CD8 ϩ T cells.…”
Section: Discussionmentioning
confidence: 94%
“…The development of OVA-specific CD8 ϩ T cells during mycobacterial infection has been studied using rBCG expressing OVA (41). Naive OVA-specific CD8 ϩ T cells differentiate into T CM cells, albeit with protracted kinetics, following infection.…”
Section: Discussionmentioning
confidence: 99%
“…6); however, on day 4, the reverse was true: briefly stimulated OT-I cells up-regulated IL-7R␣ and control OT-I cells down-regulated it (data not shown). At this time, it is unclear as to what is the reason for this delay in IL-7R␣ up-regulation on briefly stimulated OT-I cells (24,25). Overall, this staining pattern suggested that briefly stimulated OT-I cells were primarily developing into central memory-like CD8 T cells (26).…”
Section: Briefly Stimulated Cd8 T Cells Develop a Central Memory-likementioning
confidence: 98%